A survey of mosquito-borne and insect-specific viruses in hospitals and livestock markets in western Kenya - Chiuya, T.; Masiga, D.K.; Falzon, Laura C.; Bastos, A.D.S.; Fèvre, Eric M.; Villinger, J. (Public Library of Science, 2021)
Aedes aegypti and Culex pipiens complex mosquitoes are prolific vectors of arboviruses that are a global threat to human and animal health. Increased globalization and ease of travel have facilitated the worldwide dissemination of these mosquitoes and the viruses they transmit. To assess disease risk, we determined the frequency of arboviruses in western Kenyan counties bordering an area of high arboviral activity. In addition to pathogenic viruses, insect-specific flaviviruses (ISFs), some of which are thought to impair the transmission of specific pathogenic arboviruses, were also evaluated. We trapped mosquitoes in the short and long rainy seasons in 2018 and 2019 at livestock markets and hospitals. Mosquitoes were screened for dengue, chikungunya and other human pathogenic arboviruses, ISFs, and their blood-meal sources as determined by high-resolution melting analysis of (RT-)PCR products. Of 6,848 mosquitoes collected, 89% were trapped during the long rainy season, with A. aegypti (59%) and Cx. pipiens sensu lato (40%) being the most abundant. Most blood-fed mosquitoes were Cx. pipiens s.l. with blood-meals from humans, chicken, and sparrow (Passer sp.). We did not detect dengue or chikungunya viruses. However, one Culex poicilipes female was positive for Sindbis virus, 30 pools of Ae. aegypti had cell fusing agent virus (CFAV; infection rate (IR) = 1.27%, 95% CI = 0.87%-1.78%); 11 pools of Ae. aegypti had Aedes flavivirus (AeFV; IR = 0.43%, 95% CI = 0.23%-0.74%); and seven pools of Cx. pipiens s.l. (IR = 0.23%, 95% CI = 0.1%-0.45%) and one pool of Culex annulioris had Culex flavivirus. Sindbis virus, which causes febrile illness in humans, can complicate the diagnosis and prognosis of patients with fever. The presence of Sindbis virus in a single mosquito from a population of mosquitoes with ISFs calls for further investigation into the role ISFs may play in blocking transmission of other arboviruses in this region.